Pengaruh Keadilan Organisasional Terhadap Intensi Keluar pada Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi - Dani Ihsan; Syahrizal Syahrizal; Yuki Fitria (Universitas Negeri Padang, 2019)
Purpose - The aim of this research is to analyze : (1) influence of Organizational Justice to Turnover Intention (2) Influence of Organizational Justice to Job Satisfaction (3) Influence of Job Satisfaction to Turnover Intention (4) Influence Organizational Justice to Turnover Intention with Job Satisfaction as mediating variable.Methodology - The population in this research was all the employee at PT Kilang Lima Gunung which amounted to 109 people. The sampling technique of this reserach is Cluster Propotional Random Sampling Technique with total sample amounted 86 people. The data analysis technique used is multiple regression analysis with the mediating variable with SPSS version 16.0 program.Finding - The result showed that (1) Organizational Justice has negative and significant effect on Turnover Intention at employee of PT Kilang Lima Gunung.(2) Organizational Justice has positive and significant effect on Job Satisfaction at employee of PT Kilang Lima Gunung (3) Job Satisfaction has negative effect on turnover intention at employee of PT Kilang Lima Gunung (4) Job Satisfactionto mediate the influence of Organizational Justice on Turnover Intention at employee of PT Kilang Lima Gunung. Keywords: Turnover Intention, Organizational Justice, Job Satisfaction